Human pancreatic neuro-insular network in health and fatty infiltration - Tang, Shiue-Cheng; Baeyens, Luc; Shen, Chia-Ning; Peng, Shih-Jung; Chien, Hung-Jen; Scheel, David W.; Chamberlain, Chester E.; German, Michael S. (Diabetologia, 2018)
Aims/hypothesis Identification of a pancreatic neuro-insular network in mice suggests that a similar integration of islets and nerves may be present in the human pancreas. To characterise the neuro-insular network and the intra-pancreatic ganglia in a clinically related setting, we examined human pancreases in health and with fatty infiltration via 3-dimensional (3D) histology and compared the human pancreatic microenvironment with its counterpart in mice. Methods Human pancreatic specimens from individuals with normal BMI, high BMI (≥ 25) and type 2 diabetes were used to investigate the neuro-insular network. Transparent specimens were prepared by tissue clearing for transmitted light and deep-tissue fluorescence imaging to simultaneously visualise infiltrated adipocytes, islets and neurovascular networks. Results High-definition images of human islets reveal that both the sympathetic and parasympathetic nerves enter the islet core and reside in the immediate microenvironment of islet cells. Around the islets, the neuro-insular network is visualised with 3D histology to identify the intra-pancreatic ganglia (peri-lobular and intra-parenchymal ganglia) and the islet–ganglionic association. In humans, but not in mice, pancreatic fatty infiltration (BMI dependent) features adipocytes infiltrating into the parenchyma and accumulating in the peri-lobular space, in which the peri-lobular ganglia also reside. We identified the formation of adipose–ganglionic complexes in the peri-lobular space and enlargement of ganglia around adipocytes. In the specimen from the individual with type 2 diabetes, an increase in the number of nerve projections from the intra-parenchymal ganglia is associated with severe fatty infiltration. Conclusions/interpretation We present new perspectives of human pancreas and islet innervation via 3D histology. Our results strongly suggest that fatty infiltration in the human pancreas creates a neurotrophic microenvironment and promotes remodelling of pancreatic innervation.